OP0169 Apremilast, an Oral Phosphodiesterase 4 Inhibitor, is Associated with Long-Term (104-Week) Improvements in Enthesitis and Dactylitis in Patients with Psoriatic Arthritis: Pooled Results from Three Phase 3, Randomized, Controlled Trials. (9th June 2015) - Gladman, D.; Kavanaugh, A.; Adebajo, A.; Gomez-Reino, J.; Wollenhaupt, J.; Cutolo, M.; Schett, G.; Lespessailles, E.; McIlraith, M.; Hu, C.; Edwards, C.; Birbara, C.; et al.
Abstract : Background: Apremilast (APR), a PDE4 inhibitor, helps regulate immune responses in psoriatic arthritis (PsA). PALACE 1-3 compared APR efficacy/safety with placebo (PBO) in patients (pts) with active PsA despite prior conventional DMARDs and/or biologics, including efficacy assessment across multiple aspects of disease. Enthesitis and dactylitis are hallmark features of PsA that lead to pain and disability. Objectives: Evaluate the impact of APR treatment over 104 wks on enthesitis and dactylitis in a pooled analysis of PALACE 1-3. Methods: Pts were randomized (1:1:1) to PBO, APR 20 mg BID (APR20), or APR 30 mg BID (APR30) stratified by baseline (BL) DMARD use (yes/no). The PBO-controlled phase continued to Wk 24, with an early escape option at Wk 16. Double-blind APR treatment continued to Wk 52; pts could then continue to receive APR for up to an additional 4 years during an open-label extension phase. Data were pooled across PALACE 1-3 to allow for analysis of robust numbers of pts with pre-existing enthesopathy and/or dactylitis. Enthesitis was evaluated based on Maastricht Ankylosing Spondylitis Enthesitis Score (MASES) (range 0-13), which indicates the number of painful entheses out of 13 entheses sites. The dactylitis count (range 0-20) is the number of digits (hands/feet) with dactylitis present; each digit is rated as 0 (none) or 1 (present). Results: Long-term improvement in enthesitis and dactylitis severity was seen in pts with enthesitis and/or dactylitis at BL who were receiving APR at 104 weeks, as shown by reductions in MASES and dactylitis counts (Table ). Mean changes in MASES were -57.5% (APR30) and -55.1% (APR20) at Wk 104. MASES scores of 0, indicating no pain at any of the entheses assessed, were achieved by 48.7% (APR30) and 51.5% (APR20) of pts. Mean changes in dactylitis count were -80.0% (APR30) and -75.8% (APR20) at Wk 104. Dactylitis counts decreased to 0 in 77.5% (APR30) and 72.9% (APR20) of pts. Over 104 wks, most AEs were mild/moderate in severity; in general, no increase was seen in AE incidence/severity with longer term exposure. Conclusions: Over 104 wks, APR continued to demonstrate efficacy in PsA treatment, including improvements in enthesitis and dactylitis. APR demonstrated an acceptable safety profile and was generally well tolerated for up to 104 wks. Disclosure of Interest: D. Gladman Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, Celgene Corporation, Janssen, Pfizer Inc, Novartis, and UCB, Consultant for: AbbVie, Amgen, Bristol-Myers Squibb, Celgene Corporation, Janssen, Pfizer Inc, Novartis, and UCB, A. Kavanaugh Grant/research support from: Abbott, Amgen, Astra-Zeneca, Bristol-Myers Squibb, Celgene Corporation, Centocor-Janssen, Pfizer Inc, Roche, and UCB, A. Adebajo: None declared, J. Gomez-Reino Grant/research support from: Roche and Schering-Plough, Consultant for: Bristol-Myers Squibb, Pfizer Inc, Roche, Schering-Plough, and UCB SA, Speakers bureau: Bristol-Myers Squibb, Roche, Schering-Plough, and Wyeth, J. Wollenhaupt Grant/research support from: Abbott, Bristol-Myers Squibb, MSD, Pfizer Inc, and UCB, Consultant for: Abbott, Bristol-Myers Squibb, MSD, Pfizer Inc, and UCB, M. Cutolo Grant/research support from: Actelion, Bristol-Myers Squibb, and Sanofi-Aventis, Consultant for: Actelion, Bristol-Myers Squibb, and Sanofi-Aventis, G. Schett Grant/research support from: Abbott, Celgene Corporation, Roche, and UCB, Consultant for: Abbott, Celgene Corporation, Roche, and UCB, E. Lespessailles Grant/research support from: Amgen, Eli Lilly, Novartis, and Servier, Speakers bureau: Amgen, Eli Lilly, Novartis, and Servier, M. McIlraith Employee of: Celgene Corporation, C. Hu Employee of: Celgene Corporation, C. Edwards Grant/research support from: Celgene Corporation, Pfizer Inc, Roche, and Samsung, Consultant for: Celgene Corporation, Pfizer Inc, Roche, and Samsung, Speakers bureau: Abbott, Glaxo-SmithKline, Pfizer Inc, and Roche, C. Birbara Grant/research support from: Amgen, Bristol-Myers Squibb, Incyte, Eli Lilly, Merck, and Pfizer Inc, P. Mease Grant/research support from: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer Inc, UCB, Celgene Corporation, Novartis, and Roche, Consultant for: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer Inc, UCB, Celgene Corporation, Novartis, and Roche, Speakers bureau: Abbott, Amgen, Biogen Idec, Bristol-Myers Squibb, Genentech, Janssen, Eli Lilly, Pfizer Inc, and UCB,